Risk‐based planning analysis for a single levee. Issue 4 (3rd April 2016) - Hui, Rui; Jachens, Elizabeth; Lund, Jay
Abstract: Traditional risk‐based analysis for levee planning focuses primarily on overtopping failure. Although many levees fail before overtopping, few planning studies explicitly include intermediate geotechnical failures in flood risk analysis. This study develops a risk‐based model for two simplified levee failure modes: overtopping failure and overall intermediate geotechnical failure from through‐seepage, determined by the levee cross section represented by levee height and crown width. Overtopping failure is based only on water level and levee height, while through‐seepage failure depends on many geotechnical factors as well, mathematically represented here as a function of levee crown width using levee fragility curves developed from professional judgment or analysis. These levee planning decisions are optimized to minimize the annual expected total cost, which sums expected (residual) annual flood damage and annualized construction costs. Applicability of this optimization approach to planning new levees or upgrading existing levees is demonstrated preliminarily for a levee on a small river protecting agricultural land, and a major levee on a large river protecting a more valuable urban area. Optimized results show higher likelihood of intermediate geotechnical failure than overtopping failure. The effects of uncertainty in levee fragility curves, economic damage potential, construction costs, and hydrology (changing climate) are explored. Optimal levee crown width is more sensitive to these uncertainties than height, while the derived general principles and guidelines for risk‐based optimal levee planning remain the same. Key Points: A feasible risk‐based optimization model is developed for single levee planning Intermediate levee failure from through‐seepage is more frequent than overtopping levee failure Optimal levee crown width is more sensitive to varying parameters than optimal levee height